Strengthening School-Family-Community Engagement Through Community Dialogues - Amy L. Cook; Alveena Shah; Lauren Brodsky; Laura J. Morizio (Journal for Social Action in Counseling and Psychology)
Open communication among school community stakeholders strengthens collaboration and facilitates school transformation. Meaningful parent engagement through two-way conversations supports shared decision-making and developing a shared vision for change. We document the implementation and outcomes of community dialogues on race and ethnicity conducted with a group of 11 school and community members, including parents, caretakers, community professionals, and a teacher. Two rounds of semi-structured interviews with participants were conducted and analyzed using qualitative content analysis to explore outcomes of community dialogues. Critical race theory in education guided the community dialogues implementation and qualitative analyses. Findings illuminate participant appreciation for sharing narratives, becoming aware of cultural differences, and raising critical awareness to mobilize community change. Implications of school community dialogues on educational outcomes and counseling practice are also described.